Application of antiseptic composition based on polyaminopropyl biguanide in the chronic catarrhal gingivitis treatment - A. A. Kulikova; Z. S. Khabadze; Y. A. Bakaev; N. N. Fedotova; A. S. Karnaeva; Anna A. Litvinenko (LLC "Endo Press", 2022)
Inflammatory gum disease occupies a large proportion of oral diseases. Among the most honest complaints are concerns about bleeding gums, pain when eating. Gingivitis is an inflammation of the soft tissues surrounding the tooth without disturbing the gingival junction. Currently, the search for the most effective and comfortable therapy for the treatment of gingivitis remains a topical issue in medicine.Materials and methods. A group of patients with a diagnosis of K05.1 - chronic simple marginal gingivitis (chronic catarrhal gingivitis) was selected for the study. All patients underwent examination and index assessment of the condition of the marginal periodontium. Half of the patients were prescribed an antiseptic composition based on 0.2% polyaminopropyl biguanide as an auxiliary antiseptic treatment of the oral cavity. Examination and re-examination of patients was carried out on the 4th, 7th, 10th day.Results. According to the results of the examination, the diagnosis of K05.1 - chronic simple marginal gingivitis (chronic catarrhal gingivitis) was established in 77 patients aged 18 to 25 years. During the inspection on the 4th, 7th, 10th day, there were differences in the course of the disease and the values of the indices.Conclusions. The study demonstrated the effectiveness of the use of an antiseptic composition based on 0.2% polyaminopropyl biguanide in the complex therapy of chronic catarrhal gingivitis.